PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS ARTICULATE STORYLINE 3 TERHADAP MOTIVASI BELAJAR SISWA MATA PELAJARAN TIK MATERI SISTEM KOMPUTER KELAS VII - Kurrata A’yunin; Syarifudin; Ita Fitriati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using Articulate Storyline 3-based learning media on students' learning motivation in seventh-grade computer system material in Information and Communication Technology (ICT) subject. The research employed a quantitative approach with a pre-experimental design using One Group Pretest-Posttest Design, involving 20 students as the sample. The research instruments consisted of pretest, posttest, motivation questionnaires, and observation sheets. The results showed an increase in the average score from 52.25 (pretest) to 80.00 (posttest), with an N-Gain score of 0.58 categorized as moderate. The paired sample t-test indicated a significance value of 0.000 < 0.05, meaning there was a significant difference between students' scores before and after using the media. The motivation questionnaire also revealed an increase in all indicators, including learning enthusiasm, engagement, and interest in the material. Thus, the Articulate Storyline 3-based learning media was proven effective in enhancing students' learning motivation and outcomes in ICT learning. This media serves as an innovative learning solution that presents abstract material in a more visual, interactive, and engaging way, making it highly recommended for digital-based learning in junior high schools.